2013 International Conference on Informatics and Creative Multimedia 2013
DOI: 10.1109/icicm.2013.71
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing Interactive Exhibition Spaces

Abstract: Exhibition spaces are often regarded as a communal space which situates content for the pleasure of viewing. Consistent with the current development of technology emergence in digital applications, these spaces have been affected in the way that the content and tools are now being developed in the realm of digital and virtual capacity. Exploration of new media design and aesthetics has tremendously supported the new hybrid space either conceptually or visually. The local scenario is also seeing a vast particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Studies have shown that the visual experience of the visitors to an exhibition is enriched when visitors interact with exhibition space (Sharji, Peng, & Woods, 2013). The aim was to enhance the exhibition experience by merging the principles of design, architecture, and interactivity supported by digital media on an online platform (Orhun, 2014).…”
Section: Virtual Reality (Vr) Exhibitionmentioning
confidence: 99%
“…Studies have shown that the visual experience of the visitors to an exhibition is enriched when visitors interact with exhibition space (Sharji, Peng, & Woods, 2013). The aim was to enhance the exhibition experience by merging the principles of design, architecture, and interactivity supported by digital media on an online platform (Orhun, 2014).…”
Section: Virtual Reality (Vr) Exhibitionmentioning
confidence: 99%